Inflation: the problems it creates and the policies it requires - Okun, Arthur M.; Fowler, Henry H.; Gilbert, Milton (New York: New York University Press, 1970)
The book examines inflation as it relates to its problems and proffers solutions to the problems.
Includes bibliographical references.
usc 21/06/18
Loans
Keywords: Inflation (Finance); Fiscal policy; International finance; United States